PENGARUH GOOD CORPORATE GOVERNANCE, KINERJA KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2015) - Irfan Fajar Anjasmoro; Enni avitri; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the influence of good corporate governance, financial performance, and firm size on financial distress. The mechanism of good corporate governance in this study include the managerial ownership, institutional ownership, number of boards of directors, and proportion of independent board of commissioners, meanwhile the financial performance in this study are profitability and liquidity. The population taken in this study is a manufacturing company listed in the Indonesia Stock Exchange in the year 2012 to 2015 which amounted to 427 companies. From the population obtained the total of samples of 67 companies which experiencing financial distress. Data obtained by using purposive sampling method and the financial distress measured by using Altman Z-Score (1968). This study uses multiple regression analysis. The results of this study show that (1) managerial ownership had no effect on financial distress, (2) institutional ownership had negative effect on financial distress, (3) the number of boards of directors had no effect on financial distress, (4) proportion of independent board of commissioners had no effect on financial distress, (5) profitability had negative effect on financial distress, (6) liquidity had no effect on financial distress, and (7) firm size had negative effect on financial distress.Keyword : managerial ownership, institusional ownership, number of boards of directors, proportion of independent board of commissioners, profitability, liquidity, firm size, and financial distress.